SYNTHESIS OF MUTUAL PRODRUG OF P-AMINO SALICYLIC ACID (PAS) AND ISONIAZID(INH),WITH POSSIBL EENHANCEMENT PHYSICOCHEMICAL PROPERTIES - Qasir, Ahlam J; Jassim, Ahmed D (Al-Nahrain Journal of Science, 2018)
Tuberculosis is one of the most widespread disease in the world, and can be deadly in patientswith AIDS worldwide. The course of treatment is long (3-9) months, often need combinationtherapy to decrease microbial resistance, some of these drugs have serious side effects andundesirable physicochemical properties like, gastric irritation, short T1/2 (pas), hepatic toxicity andextensive metabolism by the liver (INH), through N-acetyl transferase enzyme.So by using this approach we hope reduction of gastrointestinal toxicity of PAS and reductionof intestinal acetylation of Isoniazid. This drug was synthesized by amidation of free amine groupof INH with free carboxyl group of glycine from one side and amidation of carboxyl group of PASafter protection of it, and amino group of glycine from other side, here amidation was done by usingcoupling agent (DCC) using conventional solution method and it was identified by the followingmethods: melting point, thin layer chromatography (TLC), infrared spectroscopy (IR) and theelemental analysis(CHN). The synthesized compound showed better partition coefficient comparedwith the original apromoiety (PAS,INH).